Kajian Hubungan Debit Aliran, Head Loss dan Efisiensi dalam Menentukan Kinerja Pompa Sentrifugal - Indriyani , Indriyani; Oktavitasari, Dini; Meidasari, Memey (SURYA TEKNIKA, 2026)
This research analyzes the relationship between flow velocity, head loss, and pump performance in a piping system. The performance parameters evaluated include total head, hydraulic power, and system efficiency. The research using descriptive quantitative approach through the analysis of measurement data and graphical visualization of several parameters. The results showed that head loss increases as the water flow velocity increases. A significant increase in discharge causes greater energy losses within the pipeline, which leads to a decrease in pump efficiency. Based on the evaluation results, pump 4 showed the best performance, the highest efficiency at 65.51%. Meanwhile, pump 2 showed the lowest efficiency at 34.40%. The findings indicate that there is a trade-off between increasing head loss and pump efficiency, whereas higher head loss results in lower pump efficiency. Therefore, determining the optimal operating point is essential to achieve an efficient system.